2014
DOI: 10.14569/ijacsa.2014.050803
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Challenges of Cloud Computing Adoption on Public Universities in Southwestern Nigeria

Abstract: Abstract-This study investigates the impact and challenges of the adoption of cloud computing by public universities in the Southwestern part of Nigeria. A sample size of 100 IT staff, 50 para-IT staff and 50 students were selected in each university using stratified sampling techniques with the aid of wellstructured questionnaires. Microsoft excel was used to capture the data while frequency and percentage distributions were used to analyze it. In all, 2, 000 copies of the questionnaire were administered to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Users of academic libraries are migrating onto the cloud for their information needs, and library services must migrate with them if those needs are to be met. Store expansive amounts of sensitive data and information that's easily accessible (Christopher & Temitayo, 2014).…”
Section: Discussion On the Findingsmentioning
confidence: 99%
“…Users of academic libraries are migrating onto the cloud for their information needs, and library services must migrate with them if those needs are to be met. Store expansive amounts of sensitive data and information that's easily accessible (Christopher & Temitayo, 2014).…”
Section: Discussion On the Findingsmentioning
confidence: 99%
“…Ibrahim (2014) examines nine variables in adoption cloud computing at HEIs in Nigeria, that will make decision much more easier by HEIs management as relative advantage, compatibility, complexity, trailibility, top management, firm size, amount of information, pressure coercive and quality of internet connection and also recommended Innovation Diffusion Theory. However, Christopher (2014) revealed that the adoption of cloud computing technology has an important influence on cost effectiveness, enhanced availability, low environmental impact, reduced IT complexities, mobility, scalability, increased operability and reduced investment in physical asset However, the major challenges confronting the adoption of cloud are data insecurity, regulatory compliance concerns, lock-in and privacy concerns.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [40] added the "perception, attitude and intention of people towards the adoption of cloud computing" as the most important factors in adopting cloud computing. The authors of [41] found the major factors in implementing cloud computing by public universities in Nigeria as "data insecurity, regulatory compliance concerns, lock-in and privacy concerns".…”
Section: Csfs For Cloud Computing In Institutions and E-learningmentioning
confidence: 99%